2013
DOI: 10.1111/imig.12126
|View full text |Cite
|
Sign up to set email alerts
|

The Economy of Seeking Asylum in the Global City

Abstract: This article explores asylum seeker survival strategies and agency in relation to the structural, post-industrial conditions that have emerged in Hong Kong. The focus is on the livelihoods of asylum seekers within spaces of illegality and social exclusion, how such spaces are formed, and how asylum seekers exploit local conditions to establish profitable networks across borders. The article considers asylum seekers' engagement in income-generating activities and the importance of legal status in the sectors of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…On the other hand, those asylum seekers who are fleeing persecution in their home countries are often afraid to work illegally, for fear of being deported, and can only stew for years on end. (21) It seems possible that Hong Kong authorities are using this situation to enable a flexible irregular labour force; but in any case, it seems clear that working asylum seekers significantly benefit the local Hong Kong economy (Vecchio 2016).…”
Section: How the Situation Of Hongkongers And Asylum Seekers Has Changedmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, those asylum seekers who are fleeing persecution in their home countries are often afraid to work illegally, for fear of being deported, and can only stew for years on end. (21) It seems possible that Hong Kong authorities are using this situation to enable a flexible irregular labour force; but in any case, it seems clear that working asylum seekers significantly benefit the local Hong Kong economy (Vecchio 2016).…”
Section: How the Situation Of Hongkongers And Asylum Seekers Has Changedmentioning
confidence: 99%
“…In particular, in the academic literature, asylum seekers are rarely depicted as having much agency in their host society-they may speak out about the harsh conditions under which asylum seekers live (as they do in Hong Kong: Vecchio and Beatson 2014), but they are not portrayed as having influence on the society in which they have arrived, at least not until they have become refugees and then citizens. (2) The lives of asylum seekers in Hong Kong too are generally portrayed as being bleak in academic writings (see Vecchio 2015 for the only book-length account in recent years on Hong Kong asylum seekers; see also Vecchio 2016;Mathews 2011: 78-83, 169-194;; and for a legal perspective, Loper 2010, among other writings). These portrayals were published too long ago to have depicted how asylum seekers have recently become embraced by segments of the local population in Hong Kong.…”
mentioning
confidence: 99%
“…This puts them in an extremely vulnerable and precarious situation where, on the one hand, their meager entitlement reduces them to impoverishment, while on the other hand, any attempt to work to supplement their income will immediately make them illegal and an easy target for exploitation, threats and harassment. Despite the precariousness of their situation, studies have found that they are actively involved in certain low-end industries, such as the re-cycling and garment industries and trade services, that require a transnational network (Vecchio, 2016). These industries run on an extremely tight margin and survive only “by avoiding government regulations related to minimum wage, safety and overtime conditions, and ensuring more flexibility in working hours and in the dismissal of unnecessary employees” (Vecchio, 2016: 3).…”
Section: Local Policy Context and Refugee Perspectivesmentioning
confidence: 99%
“…Despite the precariousness of their situation, studies have found that they are actively involved in certain low-end industries, such as the re-cycling and garment industries and trade services, that require a transnational network (Vecchio, 2016). These industries run on an extremely tight margin and survive only “by avoiding government regulations related to minimum wage, safety and overtime conditions, and ensuring more flexibility in working hours and in the dismissal of unnecessary employees” (Vecchio, 2016: 3). One other livelihood option for refugees or asylum seekers is self-employment.…”
Section: Local Policy Context and Refugee Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation